SEJARAH PERKEMBANGAN MADRASAH DI PAKISTAN DALAM PENDIDIKAN ISLAM MODERN - Ishmatunisa Syarif; Ayu Mukti Sari; Zahwa Nurmalita Adityas (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Madrasah is an Islamic educational institution with a long history in Pakistan, from the pre-independence era to the modern Islamic education era. This study aims to historically examine the development of madrasahs in Pakistan and their relevance in the context of modern Islamic education. The study covers the historical roots of madrasahs in the Mughal and British colonial era, post-independence developments, expansion during the Zia ul-Haq era, radicalism issues after the September 11, 2001 events, and government reform and modernization efforts. The results show that madrasahs in Pakistan have undergone complex transformations, influenced by political, social, and global dynamics. Curriculum reforms such as the Single National Curriculum (SNC) and madrasah regulation are strategic steps, but still face ideological resistance. Madrasahs in Pakistan need to continue transforming to address the challenges of Islamic education in the modern era without abandoning their Islamic identity.